Research on the framework of mathematics self-study capabilities of Vietnamese high school students - Quyen, Nguyen Van (Linguistics and Culture Review, 2021)
In general, self-study is one of the most promoting factors contributing to learning efficiency. In this report, the objective aims to build a framework of the math self-study ability of high school students. The research methodology relates to theoretical analysis through domestic and foreign studies on the overall students’ ability and Mathematics self-study capabilities; the interview includes 52 subjects (8 education experts and 44 maths teachers teaching in high schools). The final result indicates that the competency framework proposed is appropriate, necessary, and feasible for students to study on their own, helping to improve the student’s math performance. In detail, the basic competencies are Motivation, awareness, and attitude of Mathematics self-study, Knowledge of self-study in Mathematics; the Ability to generate self-study in the specific content of Mathematics.